Prospecção de ativos com ação antinociceptiva e anti-inflamatória em espécies de Myrcia DC. (MYRTACEAE) - Silva, Aline do Nascimento (2019)
The genus Myrcia contains around 700 species distributed from Mexico to Southern Brazil. Although in vitro antimicrobial, antioxidant and antinociceptive action has been described, studies involving the pharmacological potential of their volatile components are incipient. The present study aimed to analyze the chemical composition, antinociceptive and anti-inflammatory activities of essential oils from fresh Myrcia rostrata and Myrcia splendens leaves in an animal model. The oils were obtained in triplicate by hydrodistillation in a Clevenger apparatus and analyzed by Gas Chromatography/Flame Ionization Detection (GC/FID) and Gas Chromatography/Mass Spectrometry (GC/MS). Acetic acid-induced abdominal writhing, formalin-induced nociception and hot plate tests were conducted to evaluate antinociceptive activity. Anti-inflammatory activity was assessed using the formalin and glutamate-induced paw tests. Tests were conducted to evaluate acute oral toxicity and the interference of oils in the central nervous system (CNS) of animals, in addition to investigating the involvement of TRPA1, α2-adrenergic, muscarinic and opioid receptors in analgesia. The results indicated that both oils exhibited significant nociceptive and inflammation action with no signs of toxicity or interference in the motor coordination of animals, representing a promising source for the development of new drugs with anti-inflammatory and analgesic properties.